Communication Style in the Perspective of Masculine and Feminine Culture - Lani, Oktri Permata; Demina, Demina (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Communication is one aspect of human life and behavior as a whole. Humans are interconnected with one another through communication and with communication, humans can fulfill all the needs of their lives. In communicating, humans use language as a tool to express their feelings and opinions. The difference in communication style is in language understanding, where there are often differences in language understanding, this of course can lead to misunderstandings due to differences in meaning, symbols, and terms. In addition, gender also contributes to the socialization process during the growth period of a boy and a girl. Other roles can also be illustrated by the presence of sexism in the language of men and women from certain cultures. Regarding the comparison of communication styles between two different cultures, namely masculine culture (men) and feminine cultures (women), it does not show that men's communication methods are better than women's ways of communicating or vice versa. However, the differences in communication styles can be observed through certain categories, such as differences in speaking, choosing the topic of conversation, interrupting, using words or interrogative sentences, using stories and jokes, and other categories. The concept of male and female communication is like cross-cultural communication which is sometimes confusing, as when imagining two people talking but coming from two countries and even two different planets. This study aims to find out the description of the concept of gender in different communication styles between women and men.